Inferentials: The Story of a Forgotten Evidential - Delahunty, Gerald P. (Kansas Working Papers in Linguistics, 1990)
Recent work in language and text has explored such broad functional categories as evidentiality and affect, and has examined their cross-linguistic occurrences and manifestations. This paper focusses on a single construction, explores its variations, and describes and explains its pragmatic and textual functions. This rare construction, exemplified by It is that women in Ireland are not a form of prayer, occurs in several languages, denoting inferentiality, an aspect of evidentiality.